Mules and Other Monsters: Hybridity in Aristotle’s Generation of Animals - Woodcock, Norah (Phronesis, 2026)
The generation of hybrid animals, where a mother and father of two different species produce an animal that is a cross between their species, has been thought to pose a challenge to two important principles of Aristotle’s biology: that all species are fixed, and that the father transmits form to the offspring in generation. This paper argues that hybrid generation in Aristotle’s embryology does not give us grounds to reject either of these two principles, by showing that hybrid animals count as ‘monstrosities’ from Generation of Animals IV, animals who belong to the same species as their fathers despite deviating from the morphology of that species.